ANALISIS PERUBAHAN LUAS HUTAN MANGROVE DAN FAKTOR YANG MEMPENGARUHINYA DI PULAU TANAKEKE KAB. TAKALAR - Hidayat, Rahmat; Amal, Amal; Suprapta, Suprapta (Jurnal Environmental Science, 2020)
Knowing how the changes in the area of mangrove forest on Tanakeke Island, Takalar Regency in 1998 - 2018, Knowing the factors that influence changes in the area of mangrove forests on Tanakeke Island, Takalar Regency.Analysis of changes used is remote sensing image analysis. The imagery used is LANDSAT 5 TM satellite imagery acquisition in 1998, LANDSAT 7 + ETM satellite imagery acquisition in 2008 and LANDSAT 8 imagery OLI acquisition in 2018. Guided classification method with maximum like-lihood method is used to determine changes in mangrove forest area, while for activity factors humans that affect changes in mangrove area are analyzed in terms of percentage descriptions. The area of Tanakeke Island's mangrove forests in 1998 was 3,309.93 hectares, in 2008 it was 2,699.2 hectares, which was reduced by 621.91 hectares. And in 2018 the area will be 2,421.38 hectares and the total change in the area of mangove forests will be reduced by 908.55 hectares. The factors of human activity that affect changes in the area of mangrove forests most importantly is the conversion of mangrove forest land into ponds and uncontrolled collection of firewood for firewood.